1996
DOI: 10.1002/(sici)1096-9861(19961111)375:2<303::aid-cne9>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides and neurotrophin receptor mRNAs primary sensory neurons of aged rats

Abstract: Neuropeptides and neurotrophin receptors are regulated in primary sensory neurons in response to axonal injury, and axonal lesions are characteristic stigmata of aging primary sensory neurons. We have therefore examined the expression of neuropeptides and neurotrophin receptor mRNAs in 30-month-old (median survival age) Sprague-Dawley rats to see if similar adaptive mechanisms operate in senescence. The content of neuropeptides was examined with immunohistochemistry (IHC) and in situ hybridization (ISH), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 104 publications
(91 reference statements)
1
17
1
Order By: Relevance
“…This supports the suggestion that NGF acts on the nociceptive afferent to induce mechanical hyperalgesia and that TrkA is the NGF receptor on primary afferent nociceptors at which NGF acts to produce mechanical hyperalgesia. Our studies do not rule out a role for the p75 neurotrophin receptor, which is also found in primary afferent nociceptors (Bergman et al, 1996). Indeed, in our preliminary behavioural experiments, we found that while there was a detectable inhibition of NGF-induced hyperalgesia in the presence of antisense oligodeoxynucleotide against p75, such inhibition was much smaller in magnitude than the inhibition we observed using antisense targeting TrkA (unpublished observations).…”
Section: Discussioncontrasting
confidence: 74%
“…This supports the suggestion that NGF acts on the nociceptive afferent to induce mechanical hyperalgesia and that TrkA is the NGF receptor on primary afferent nociceptors at which NGF acts to produce mechanical hyperalgesia. Our studies do not rule out a role for the p75 neurotrophin receptor, which is also found in primary afferent nociceptors (Bergman et al, 1996). Indeed, in our preliminary behavioural experiments, we found that while there was a detectable inhibition of NGF-induced hyperalgesia in the presence of antisense oligodeoxynucleotide against p75, such inhibition was much smaller in magnitude than the inhibition we observed using antisense targeting TrkA (unpublished observations).…”
Section: Discussioncontrasting
confidence: 74%
“…This pattern of altered mechanical sensitivity combined with a reduced number of mechanoresponsive unmyelinated C-fibers is also observed in aging 28,29,51,53 and diabetic neuropathy, 18,36 and may also correspond with reports of small-fiber polyneuropathy in some patients diagnosed with fibromyalgia 32 and restless legs syndrome. 38 These changes seem to be related with decreased neurotrophic factors in primary sensory neurons, 3,18 however, in a reserpine-induced pain model, no apparent histological changes were detected in the sciatic nerve bundle and DRG by light microscopy, 27 which suggests that this paradoxical change in mechanical sensitivity likely results from reserpine-mediated functional alterations in the peripheral nervous system.…”
Section: Peripheral Mechanisms Of Altered Nociceptionmentioning
confidence: 99%
“…Changes in the peripheral nociceptive pathways with age have also been studied: decrease in the number of thin-fiber afferents (Nakayama et al, 1998;Azcoitia et al, 2003), conduction velocity (Sato et al, 1985), and sensory neurons containing neuropeptides (Bergman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%